Polyhedral oligomeric silsesquioxane-supported ionic liquid for designing nanostructured hybrid organic-inorganic networks. (May 2019) - Chabane, Houssém; Livi, Sébastien; Benes, Hynek; Ladavière, Catherine; Ecorchard, Petra; Duchet-Rumeau, Jannick; Gérard, Jean-François
Graphical abstract: The molecular design of nanostructured epoxy-amine networks by using IL-grafted POSS as inorganic-organic nano-building blocks. Abstract: In this work, two polyhedral oligomeric silsesquioxane-supported imidazolium ionic liquid have been successfully synthesized and used as organic-inorganic hybrid nano-objects in order to design nanostructured epoxy-amine networks. In fact, two partially condensed POSS have been covalently grafted with an ionic liquid-functionalized silane. The thermal properties of the ionic liquid (IL)-modified POSS have highlighted a significant enhancement of the thermal stability (400 vs 300 °C). Then, these hybrid organic-inorganic nano-objects (5 wt%) have been incorporated into a conventional epoxy prepolymer (diglycidyl ether of bisphenol A) which was copolymerized with the isophorone diamine in order to prepare nanostructured networks. Thus, an excellent dispersion of the IL-functionalized POSS was obtained in the thermosetting networks, characterized by the formation of spherical or ellipsoïdal inorganic-rich nanoparticles with nanoscale sizes (10–80 nm).